PENGARUH PENGGUNAAN MULTIMEDIA TERHADAP MOTIVASI BELAJAR MAHASISWA PADA PERKULIAHAN PENGANTAR MANAJEMEN DI PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Amborowati, Arum Dwi; Kartikowati, Sri; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe use of multimedia in the learning process can improve the attractiveness and attention of the students to understand the lesson. Multimedia is expected to increase the students motivation so that the learning process can be run in accordance with the objectives that have been formulated. This study aims to determine the level of the comparison and the effect of using multimedia on students’ motivation in the course of Introduction to Management at the Faculty of Education, University of Riau. Respondent are student who attending the course of Introduction of Management, total 34 students. The data used primary data and secondary data. The data is collected using technique questionnaire. The data then is analized using the formula of relative frequency and hypothesis is verified using t-test. The results showed value = 20,760, df =33, = 2.034. As a result, the t-test mentioned that value greater than 20,760 > 2,034 ( > ), meaning there is a positive effect of the use of multimedia to students motivation at the class of PE-B to learn the Introduction of Management.Key words : multimedia; motivation to study; college student; university; education